Competing for legitimacy in the place branding process: (re)negotiating the stakes. (August 2022) - Reynolds, Laura; Koenig-Lewis, Nicole; Doering, Heike; Peattie, Ken
Abstract: Although stakeholder participation in place branding is actively encouraged, there has been a paucity of studies examining why uneven involvement persists in practice. This study builds on Bourdieu's theory of field and capital to explain how stakeholders from the local state, destinations, businesses and local communities negotiate influence and legitimacy in the place branding process. A multi-case study of two UK cities was employed involving semi-structured interviews with 60 stakeholders. We identify the specific characteristics of cultural capital in place branding: procedural know-how and place-sensitive knowledge. Our findings show that community representatives can acquire a seat at the place branding table by possessing distinct place-sensitive knowledge and drawing on procedural know-how accrued from professional settings. Nevertheless, traditionally dominant stakeholder groups, such as local state actors, destination management organisations and the business community, can build strategic collaborations that counter deficits in cultural capital and thus retain their status. Highlights: Power relations are replicated despite claims of inclusive place branding processes. Stakeholders compete for legitimacy utilising social and cultural capital. Procedural know-how and place-sensitive knowledge establish cultural capital. Community representatives utilise cultural capital to gain influence in the process. Local state actors and DMOs use social capital to counter cultural capital deficits.